2011
DOI: 10.1126/scisignal.4155tr1
|View full text |Cite
|
Sign up to set email alerts
|

Signaling by Neuronal Swelling

Abstract: Several physical phenomena accompany the firing of electrical impulses by axons. Some of these, such as the microscopic swelling of axons, alter the transmission of light through axons. This produces what are called “intrinsic optical signals” because optical methods can be used to see axons fire without adding voltage-sensitive dyes or using electronic amplifiers. These physical changes allow neurons to communicate through nonsynaptic signals to adjacent cells, such as other neurons or glia. Two of the three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…suggesting that perfusion is a potential contributor of the observed dfMRI changes. We further observed that dfMRI activations were mostly located in GM but also had a large component in WM, where swelling has been shown as a mechanism implicated in neuronal transmission (Fields, 2011). Changes in T 2 * appear to have a limited influence on the dfMRI signal, provided that the detected activations were not fully included in those derived from GE-BOLD but rather exhibited an alternative spatial pattern, as suggested by the limited overlap values equal to 45 ± 14%.…”
Section: Discussionmentioning
confidence: 64%
“…suggesting that perfusion is a potential contributor of the observed dfMRI changes. We further observed that dfMRI activations were mostly located in GM but also had a large component in WM, where swelling has been shown as a mechanism implicated in neuronal transmission (Fields, 2011). Changes in T 2 * appear to have a limited influence on the dfMRI signal, provided that the detected activations were not fully included in those derived from GE-BOLD but rather exhibited an alternative spatial pattern, as suggested by the limited overlap values equal to 45 ± 14%.…”
Section: Discussionmentioning
confidence: 64%
“…Pioneering work more than 40 years ago provided the first evidence for microscopic swelling of axons during firing of APs (20,21), leading to changes in light reflectivity of brain tissue in response to neuronal activity (22,23). These changes reflect transient osmotic effects caused by the flow of ions and water molecules across the axolemma during AP depolarization and repolarization, where the axonal volume typically recovers quickly after the end of AP firing.…”
Section: Discussionmentioning
confidence: 99%
“…High frequency stimulation typically leads to net accumulation of Na + and Cl − and swelling of somata and axonal processes and dendritic spines (see for example [12, 63, 203]). Douglas Fields proposed that in the axonal regions, the activity-dependent swelling may be functionally important for communication between axons and surrounding glial cells, and involve release of neuroactive molecules, presumably via VRAC [62]. Under physiological and supraphysiological conditions, changes in neuronal volume are quite small which make it difficult to differentiate them from changes in the surrounding glial cells.…”
Section: Common and Unique Roles Of Vrac Within The Brainmentioning
confidence: 99%